Agroforestry, the solution to food insecurity for rural communities in Vanuatu - André, Glarinda (Technical Centre for Agricultural and Rural Cooperation, 2018)
Agroforestry, the process of surrounding agricultural land with trees and shrubbery, was implemented in a conservation area in Vanuatu in 2012 with the aim of ending food insecurity in the rural community of Khole. With 50 plots established in the 420 ha area, local farmers gained the ability to grow resilient variations of kumala and yam.